2022
DOI: 10.1007/s00167-022-07007-1
|View full text |Cite
|
Sign up to set email alerts
|

The orientation of the ALL femoral tunnel to minimize collision with the ACL tunnel depends on the need or not of far-cortex drilling

Abstract: Purpose To (1) evaluate the optimal drill orientation of the anterolateral ligament (ALL) femoral tunnel to minimize collision with the anterior cruciate ligament (ACL) femoral tunnel during anatomical ACL reconstruction according to the need for far-cortex drilling and (2) investigate the geometric factors that afect tunnel collision secondary to drill orientation of the ALL femoral tunnel. Methods A three-dimensional femoral model of patients who underwent anatomical single-bundle ACL reconstruction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Many studies have shown a high percentage of tunnel convergence in ACL and ALL reconstruction and recommended that the ALL tunnel be oriented at specific angles to avoid convergence. 9,11,12,19 In our study, tunnel convergence could be effectively avoided if the ALL tunnel were placed at anterior and distal angles .24°. This result was similar to that in the study by Moon et al 12 for procedures not requiring far cortex drilling.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Many studies have shown a high percentage of tunnel convergence in ACL and ALL reconstruction and recommended that the ALL tunnel be oriented at specific angles to avoid convergence. 9,11,12,19 In our study, tunnel convergence could be effectively avoided if the ALL tunnel were placed at anterior and distal angles .24°. This result was similar to that in the study by Moon et al 12 for procedures not requiring far cortex drilling.…”
Section: Discussionmentioning
confidence: 79%
“…9,11,12,19 In our study, tunnel convergence could be effectively avoided if the ALL tunnel were placed at anterior and distal angles .24°. This result was similar to that in the study by Moon et al 12 for procedures not requiring far cortex drilling. In our study, there was no significant difference in the ACL femoral tunnel between groups.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations